2013
DOI: 10.1002/lary.24447
|View full text |Cite
|
Sign up to set email alerts
|

The vestibulo‐ocular reflex and subjective balance after vestibular schwannoma surgery

Abstract: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…In light of our findings, one can predict that patients who compensate with a “gathered pattern” saccadic strategy, with covert saccades always with the same latency, will have lower levels of disability (8) and postural instability, compared to those with a “scattered” saccadic strategy.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In light of our findings, one can predict that patients who compensate with a “gathered pattern” saccadic strategy, with covert saccades always with the same latency, will have lower levels of disability (8) and postural instability, compared to those with a “scattered” saccadic strategy.…”
Section: Discussionmentioning
confidence: 71%
“…This PR score reflects the amount of organization of refixation saccades across sequential head impulses and, indirectly, the level of vestibular disability of the patients as measured by the Dizziness Handicap Inventory (8). Saccadic reorganization is thus a useful marker of vestibular compensation following a complete unilateral vestibular ablation (18, 20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Batuecas et al found 22 % of patients who displayed an abnormal VOR gain were related to randomly appearance of covert and overt saccades, and these patients report higher level of vestibular disability and handicap. The author concludes that randomly appearance of covert and overt saccades on postoperative schwannoma excision were associated with poorer compensation after the surgery [39]. There is no reported data showing the comparison between VEMP and vHIT in VS.…”
Section: Role Of Vhit In Vestibular Schwannoma (Vs)mentioning
confidence: 95%